USING BABY BUS YOUTUBE TO ENHANCE STUDENTS’ VOCABULARIES: An Experimental Research - Inayah , Nurahdatul; Akib, Erwin; Muhsin, Muhammad Arief (Journal of Computer Interaction in Education, 2018)
This research aimed to find out is the implementation of Baby Bus You Tube to enhance the students’ vocabulary in seventh grade of SMP Negeri 1 Tinggi Moncong or not. It was emphasized on the improvement of the students’ vocabulary in English by using Baby Bus YouTube video. The research applied a Pre-experimental Method, with one group Pre-test and Post-test design, which consisted of six meeting, includes the treatments. The sample was taking by purposive sampling technique and the total of number of sample was 26 students in class 7.3. The data was obtained by using translate words and matching words. The findings of research were the mean score of the students development to their vocabulary was 5.85 in Pre-test and become 6.73 in Post-test. The students development their vocabulary is 15.23% It is supported by the value of t-test that is bigger than the value of t-table (2.226>2.059). Therefore, the Alternative was accepted and Null Hypothesis was rejected. Based on the result analysis, the researcher concludes that Using Baby Bus YouTube is Enhance students’ vocabulary to the seventh grade of SMPN 1Timggimoncong, Gowa. It implies that the Baby Bus YouTube videos are affective to improve the students’ vocabulary